Synthesis, characterization and biological activity of organometallic derivatives of the antimalarial drug mefloquine as new antischistosomal drug candidates. Issue 11 (18th October 2018) - d'Orchymont, Faustine; Hess, Jeannine; Panic, Gordana; Jakubaszek, Marta; Gemperle, Lea; Keiser, Jennifer; Gasser, Gilles
Abstract : The design, synthesis, characterization and biological evaluation of new ferrocenyl and ruthenocenyl derivatives of the antimalarial mefloquine is described. Abstract : We present the design, synthesis, characterization and biological evaluation of new ferrocenyl and ruthenocenyl derivatives of the organic antimalarial mefloquine, a drug also known for its antischistosomal activity. The two metallocenyl derivatives prepared (3 and4 ) demonstrated comparable activity to mefloquine against adult-stage Schistosoma mansoni in vitro . Importantly, both compounds were found to have lower toxicity in all cell lines than mefloquine itself. Administration of a 200 mg kg −1 oral dose of3 and4 to S. mansoni -infected mice did not significantly reduce worm burden, contrary to mefloquine.